2004
DOI: 10.1590/s1415-54192004000600010
|View full text |Cite
|
Sign up to set email alerts
|

Análise in vitro da resistência ao cisalhamento de braquetes metálicos colados em incisivos bovinos e humanos

Abstract: O objetivo deste trabalho foi comparar a resistência ao cisalhamento de braquetes metálicos fixados em esmalte bovino e humano e observar o índice de remanescente de adesivo (IRA). A amostra consistiu de 30 dentes divididos em três grupos, formados por incisivos inferiores permanentes humanos, incisivos inferiores permanentes bovinos e incisivos inferiores decíduos bovinos. Foi realizada profilaxia com pedra-pomes e água, seguida de condicionamento do esmalte com ácido fosfórico a 37%, em todos os dentes. Fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 10 publications
1
14
1
5
Order By: Relevance
“…Regarding the post-fixation time, there was no statistical significant difference between 10 minutes and 24 hours tests, except for Transbond Plus Color Change, as observed in other study [21]. Thus, the hypothesis that it would be no influence of postfixation time on SBS values could partially be validated.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Regarding the post-fixation time, there was no statistical significant difference between 10 minutes and 24 hours tests, except for Transbond Plus Color Change, as observed in other study [21]. Thus, the hypothesis that it would be no influence of postfixation time on SBS values could partially be validated.…”
Section: Discussionmentioning
confidence: 49%
“…The minimum shear bond strength of an adhesive should be between 5.9 and 7.9 MPa to be considered adequate for clinical needs, and at least 4.9 MPa for laboratory studies [20,21]. When the results of this study were compared with these reference values, it was found that all materials evaluated comply with these values, considering both periods.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, our results confront studies which reported the majority of disruptions in the interface composite/ bracket. 4,15,16,19,24 After shear bond strength test and during the ARI evaluation enamel fractures were observed in four specimens distributed among the four groups. This relative frequency of fractures among groups, supported by the study by Liu et al, 10 may be associated with high strength supported by the samples.…”
Section: Resultsmentioning
confidence: 99%
“…19 Several bonding materials have been used, including composites which have good resistance, toughness and dimensional stability. 8 Advantages to use light-curing resin in orthodontic procedures include reduced risk of contamination and increased accuracy in positioning the bracket, compared to the use of self-curing resin.…”
Section: Introductionmentioning
confidence: 99%
“…A opção por este tipo de dente se deu pela facilidade de obtenção de uma amostra grande com maior homogeneidade quanto à idade dos dentes extraídos (animais com menos de 5 anos de idade) e que tinham um tempo de aproximadamente 1 mês após a extração (ABNT, 2014). Estudos comparando a utilização de dentes bovinos e humanos demonstraram que os incisivos bovinos são substitutos adequados para ensaios de adesão ao esmalte, tanto para avaliação da resistência, em megapascal, quanto para avaliação do índice de remanescente de adesivo (REIS et al, 2004;ROMANO et al, 2004).…”
Section: Discussionunclassified